Policy Paradoxes in Environmental Sustainability: The Interplay of Socio-Economic Factors, Policy Innovations, and Community Forestry in Thailand - Chaiya, Chitralada (Journal of Ecohumanism, 2024)
Environmental sustainability and climate mitigation are global priorities requiring innovative policies that balance ecological conservation with socio-economic development. This study examines the interplay between Thailand's greenhouse gas emissions trading, community forestry, and their combined impact on sustainable development through multiple regression analysis. Results reveal a paradox: renewable energy consumption negatively impacts community forests, suggesting land-use competition and policy misalignment. Increased R&D expenditure enhances community forestry, showing the transformative potential of targeted innovation. Income disparity undermines community forestry efforts, highlighting the need for inclusive policies addressing socio-economic inequalities. The positive correlation between CO2 emissions and community forestry extent questions the efficacy of current carbon offset initiatives. This study urges policymakers to adopt a nuanced approach, aligning renewable energy expansion with forestry conservation and addressing socio-economic disparities. These insights challenge conventional sustainability paradigms, advocating for comprehensive policy frameworks to achieve genuine sustainable development and effective climate mitigation.